Resistance of Hibiscus x moscheutos L. to biostressors in the south of Russia - Tyshchenko Evgenia; Prakh Svetlana; Podgornaya Marina (BIO Web of Conferences, 2022)
16 varieties and 2 hybrid forms of Hibiscus x moscheutos L. have been studied for adaptability to biostressors. It was found that in the conditions of the south of Russia, root rot is most often found from pathogens (Fusarium equiseti (Corda) Sacc., Phytophthora sp.) on hibiscus plants. An assessment of the field resistance of hibiscus varieties to root rot and phytophagans was carried out. It was revealed that the maximum harmfulness to Hibiscus x moscheutos L. was noted in pests: Hilicoverpa armigera L., Padagrica fuscicornis L., and Altica oleracea L. Helicoverpa zea caterpillars primarily damage varieties with red and bright pink flowers: Cranberry Crush, Heartthrob, etc. (2-3 points). Varieties with white, white-pink petals:Old Yella, Peppermint Shnaps, etc. were damaged by helicoverpa zea to a weak degree (0-1 point). The main harmfulness of ground psylla is noted in June, the maximum damage score was recorded in varieties with a thin leaf blade: Heartthrob, Robert Fleming, hybrid D-200 (4 points), varieties with dense leaf texture were slightly damaged: Peppermint Shnaps, Fantasia (1 point). The obtained data on the degree of impact of biostressors on hibiscus plants allows to develop an effective protection system for growing hibiscus.